Characterization of Left Ventricle Main Flow Axis Line Using Echodynamography - Sri Oktamuliani; Kaoru Hasegawa; Tadanori Minagawa; Yoshifumi Saijo (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
Left ventricular (LV) blood flow analysis may play an essential role in evaluating cardiac function besides the classical analysis of wall motion. Echodynamography is an imaging method in which two-dimensional (2D) blood flow vectors are deduced by blood flow information obtained by color Doppler echocardiography. Echodynamography has provided useful information on the blood flow pattern in healthy and abnormal LV. The main flow axis line (MFAL) is defined as a maximum velocity magnitude of blood flow from the LV's apex to LV's outflow, which is a new hemodynamic parameter for cardiac assessment. The present study's objective is to compare blood flow patterns between healthy and abnormal LV by investigating the MFAL and its correlation to vorticity and velocity distribution on MFAL. This study enrolled 12 participants, four healthy volunteers, and eight abnormal patients. Echodynamography analyzed frame by frame Doppler image of apical three-chamber views. The results showed MFAL superimposed on vorticity mapping during ventricular ejection and MFAL path coincide with the irrotational flow of zero vorticity path, ω = 0. A significant difference was observed in the velocity distribution curve (VDC) on the MFAL during early, mid, and late systoles compared to healthy and abnormal LV. VDC showed the linear upward curve and the highest velocity magnitude during the early systole phase in healthy LV. In contrast with abnormal LV, VDC showed the downward convex curve and the highest velocity magnitude during mid systole phase. Furthermore, the gradient and slope angle of the VDC on the MFAL was compared. The result showed that the maximum gradient and slope angle were not significantly different between healthy and abnormal LV. In conclusion, the study of MFAL and the correlation to vorticity based on the Echodynamography computational program provides additional insights for representing a cardiac function, and thus, the clinical implications of MFAL warrant further investigation.